Morphological screening of rice varieties growing in Assam resistance to aluminium toxicity - Rahman, Runa; Hussain, Safiqul; Upadhyaya, Hrishikesh (Current Botany, 2025)
When plants are exposed to low pH levels, aluminium, which is unnecessary for plant growth, can be harmful. This experiment was conducted to study the aluminium toxicity induced responses among the 100 rice varieties growing in Assam, India. The rice seeds were grown hydroponically in Hoagland’s solution and 10 day old seedlings were subjected to 50 and 100μMAlCl3 treatment for 7 days and various growth parameters (viz., root length, shoot length, root fresh weight, shoot fresh weight, root dry weight, shoot dry weight) were recorded. Based on the overall morphological parameters, the aluminium Stress Response Index (SRI) was calculated. Again, iPASTIC software is also used to calculate various tolerance indices. Our experiment identified the Al-tolerant and Al-sensitive rice varieties based on the growth performance. Our findings lead us to conclude that both the Stress Response Index and iPASTIC can be used as a useful method for sorting among a wide range of rice cultivars to assess each variety’s resistance to a particular abiotic stress.